Badanie Stanu Naprężenia Wałów z Krążkami - Kepicz, T.Ju.; Sawczenko, W.I. (Engineering Transactions, 1972)
The paper presents the results of experimental investigations of the stresses due to torsion and bending of a shaft with a constant circular cross-section; the shaft is equipped with one or three disks forged together with the shaft. This type of shafts is frequently applied in turbine structures. The photo-elastic investigations took into account the spatial state of stress. The stress distributions and their concentrations are shown in diagrams; the analysis of the results presented in the paper allows for drawing some interesting conclusions of practical importance.